Control of underwater acoustics using anisotropic solid metamaterials with continuously tuned material axes. (October 2019) - Cheng, Yong; Yu, Tianjun; Zhou, Xiaoming
Abstract: Inertial transformation acoustics is a method for deriving a spatial pattern of material parameters for use in the arbitrary regulation of acoustic trajectories. This work highlights the discussion on a general metamaterial model with material properties that meet all the needs of the inertial transformation parameters. The proposed solid metamaterials are described to possess broadband anisotropic density and continuously tuned material axis while exhibiting fluid-like elasticity, namely, isotropic bulk stiffness and sufficiently small shear resistance. In particular, the metamaterial structure embodies a regular cell shape with an unaltered profile against the rotation of material axes, which facilitates the assembly of functional devices. An underwater acoustic rotator is designed and numerically verified to elucidate the wave dispersion and effective-medium characteristics of the metamaterial. A guideline for constructing the transformation device from the basic cells is also provided herein. The presented model can serve as a new material platform on the exploration of arbitrary acoustic-control via the inertial transformation method.